Effects of epigallocatechin gallate on the stability, dissolution and toxicology of ZnO nanoparticles. (1st March 2022) - Cao, Wandi; Gu, Manyu; Wang, Shuyi; Huang, Chaobo; Xie, Yixi; Cao, Yi
Highlights: EGCG changed ZnO NPs' AFM height, solubility in cell culture medium, hydrodynamic size and PDI. EGCG almost completely reversed the cytotoxicity of ZnO NPs to 3D Caco-2 spheroids. EGCG reduced Zn ions and altered GO terms related with endocytosis and exocytosis in NP-exposed spheroids. EGCG altered signaling pathways related with functions with mitochondria, ER and lysosomes. Abstract: Previously we reported the cytoprotective effects of polyphenols rich in hydroxyl groups against ZnO nanoparticles (NPs). This study used RNA-sequencing to evaluate the toxicity of ZnO NPs and epigallocatechin gallate (EGCG) to 3D Caco-2 spheroids. EGCG altered the colloidal stability of ZnO NPs, shown as the changes of atomic force microscopic height, solubility in cell culture medium, and hydrodynamic sizes. EGCG almost completely reversed ZnO NP-induced cytotoxicity, and consistently, alleviated ZnO NP-induced gene ontology (GO) terms and genes related with apoptosis. EGCG also modestly decreased intracellular Zn ions and changed GO terms and genes related with endocytosis/exocytosis in ZnO NP-exposed spheroids. Meanwhile, EGCG changed ZnO NP-induced alteration of GO terms and genes related with the functions of mitochondria, endoplasmic reticulum and lysosomes. We concluded that EGCG alleviated the cytotoxicity of ZnO NPs to 3D Caco-2 spheroids by altering NPs' colloidal properties and the pathways related with internalization and organelle dysfunction.